2009
DOI: 10.1093/jxb/erp198
|View full text |Cite
|
Sign up to set email alerts
|

Salt stress-induced alterations in the root proteome of barley genotypes with contrasting response towards salinity

Abstract: In addition to drought and extreme temperatures, soil salinity represents a growing threat to crop productivity. Among the cereal crops, barley is considered as notably salt tolerant, and cultivars show considerable variation for tolerance towards salinity stress. In order to unravel the molecular mechanisms underlying salt stress tolerance and to utilize the natural genetic variation of barley accessions, a series of hydroponics-based salinity stress experiments was conducted using two genetic mapping parents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
151
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 198 publications
(160 citation statements)
references
References 53 publications
6
151
1
2
Order By: Relevance
“…Sobhanian et al (2010) reported that FRK was down-regulated in the hypocotyls/root of soybean (salt-susceptible) under NaCl treatment. FRK was down-regulated in response to salt stress in barley cultivars (Witzel et al 2009) whereas upregulation of FRK was observed in our present study on H. marinum (as a salt-tolerant wild barley). Therefore, we can suggest that upregulation of fructokinase and cyMDH could elevate plant tolerance to abiotic stress by improving the energy metabolism pathways.…”
Section: Energy Metabolismcontrasting
confidence: 46%
“…Sobhanian et al (2010) reported that FRK was down-regulated in the hypocotyls/root of soybean (salt-susceptible) under NaCl treatment. FRK was down-regulated in response to salt stress in barley cultivars (Witzel et al 2009) whereas upregulation of FRK was observed in our present study on H. marinum (as a salt-tolerant wild barley). Therefore, we can suggest that upregulation of fructokinase and cyMDH could elevate plant tolerance to abiotic stress by improving the energy metabolism pathways.…”
Section: Energy Metabolismcontrasting
confidence: 46%
“…Overexpression of Gly I and Gly II in transgenic plants inhibits an increase in MG level under Zn and salt stress condition and confers tolerance to heavy metal and high salt by increasing the GSH based detoxification system and decreasing lipid peroxidation (Veena et al 1999;Singla-Pareek et al 2003;Yadav et al 2005a, b). A proteomic study of salt-tolerant barley also showed higher Gly I protein expression under salinity stress conditions (Witzel et al 2009). In the present study, we observed a slight increase in Gly I activity while the Gly II activity decreased (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Protein concentration was estimated with the Plus One 2D-Quant Kit (GE Healthcare). 2-DE and protein staining were performed according to Witzel et al (2009), with the following modifications: 50 µg of TAC proteins were loaded on immobilized pH gradient dry gel strips (7 cm, pH gradient 3 to 10; GE Healthcare). The second dimension was performed on 11.25% (w/v) polyacrylamide gels containing 0.1% (w/v) of SDS.…”
Section: Two-dimensional Separation Of Tac Proteins and Mass Spectrommentioning
confidence: 99%
“…Separated proteins were stained with colloidal Coomassie Brilliant Blue (Gel Code Blue; Thermo Fisher Scientific). Protein spots were manually excised and trypsin digested (Porcine Sequencing Grade; Promega) as described (Witzel et al, 2009). Acquisition of peptide mass fingerprint data and corresponding LIFT spectra was performed using an ultrafleXtreme matrix-assisted laser desorption/ionization time-of-flight device (Bruker Daltonics) equipped with a Smartbeam-II laser with a repetition rate of 1000 Hz.…”
Section: Two-dimensional Separation Of Tac Proteins and Mass Spectrommentioning
confidence: 99%